Donor HLA Genotyping using Polymerase Chain Reaction- Sequence Specific Primers (PCR-SSP) as Method for Acquiring Donor Panel in Platelet Refractoriness - Tubagus Djumhana Atmakusuma; Andhika Rachman; Ni Ken Ritchie (Molecular and Cellular Biomedical Sciences, 2021)
Background: Evaluation and identification of HLA antibodies in the recipient’s serum is of utmost importance prior to transplantation and transfusion. HLA typing is a steppingstone in proposing a donor panel. In order to obtain the HLA typing, Polymerase Chain Reaction-Sequence Specific Primers (PCR-SSP) can be performed.Materials and method: This is a preliminary study to determine HLA polymorphism by HLA genotyping in 43 blood donors. DNA from the samples was isolated using commercial kits according to the standard protocol. The DNA then was amplified using PCR-SSP methods and analyzed using the provided set in the kit.Results: This study found that the most frequent HLA-A alleles was HLA-A*24 (41.9%). For HLA-B alleles, the most common was HLA-B*15 (28%). Most frequent HLA-A-B haplotypes was HLA-A*24-B*15 (11.3%). The results from this study concurs with that of previous study. However, some alleles might vary due to difference in study population. Determining HLA-typing is of paramount importance in an ethnically diverse country such as Indonesia. In contrast to homogenous caucassian country, difference in ethnicity might cause platelet refractoriness due to incompatibility. HLA-typing would also guide the diagnostic workup and required treatment strategy for platelet refractoriness.Conclusion: From the HLA typing using PCR-SSP in blood donors in Jakarta, we found that the most frequent alleles were HLA-A*24 and HLA-B*15; and the most frequent haplotypes were HLA-A*24-B*15. This study should be upscaled to include larger population and ethnic groups to obtain complete profile of Indonesian population.Keywords: platelet refractoriness, HLA, donor, PCR-SSP, transfusion medicine